Developing an integrated model of Islamic social finance: toward an effective governance framework - Widiastuti, Tika; Ningsih, Sri; Prasetyo, Ari; Mawardi, Imron; Herianingrum, Sri; Hady, Aufar Fadlul; Robani, Anidah; Al Mustofa, Muhammad Ubaidillah (Elsevier Ltd, 2022)
This study proposed an integrated model of Islamic Social Finance (ISF) to accelerate the transformation of the poor toward prosperity. This is a qualitative and quantitative approach using grounded theory and the Average Weighted Index (AWI). The integration model of Islamic social finance is implemented through 4 ER (Economic Rescue, Economic Recovery, Economic Reinforcement, and Economic Resilience) by integrating Islamic social finance instruments in a joint project scheme. The additional finding of the empirical investigation shows that integrated Islamic social finance is 12% more effective in enriching the poor than the non-integrated program. This study emphasizes the significance of integrating Islamic social finance in accelerating the well-being of the poor community.